Environmental sustainability and postulates of thermodynamics: an essay from the work of Nicholas Georgescu-Roegen - Barbosa, Leila Cristina Aoyama; Marques, Carlos Alberto (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This essay discusses the environmental sustainability theme from the Second Law of Thermodynamics - Entropy Law - with reference to the discussions of the economist and mathematician Nicholas Georgescu-Roegen on the environmental limits to economic development. When considering the entropy as the most economical of all physical laws, the author analyzes the inevitable consequences of entropic processes of human activities, criticizing the theory of balance between the environment and economic development, calls into question the very concept of sustainable development. The theoretical bases of their ideas, based on the classic postulates of the natural sciences, have important contributions for the critical perspective of environmental education and for the science education.